THE EFFECT OF L-CARNITINE ON IMPROVING SEMINAL FLUID PARAMETERS IN MALE INFERTILITY (Iraqi Journal of Medical Sciences, 2016)
Background:L-carnitine is an important antioxidant present in a high concentration in epididymal fluid. It supplies energy for sperms to acquire their motility in the epididymis.Objective:To evaluate the effect of L-carnitine on improving some of the seminal fluid parameters in infertile males.Methods: Ninety-six infertile males were divided into two groups, a group received L-carnitine and the other group received multivitamin. Seminal fluid analysis performed before and after treatment in both groups. Analysis and comparison of the results were carried out between both groups for all patients then for patients with primary and secondary infertility in each group.Results:The patients received L-carnitine showed no improvement in semen volume but a significant raise in sperm concentration observed in all patients. A highly significant raise of sperm motility was observed especially in patients with primary infertility.Conclusion:L-carnitine significantly improves sperm concentration and sperm motility especially in patients with primary infertility. It is recommended for oligoasthenozoopermic infertile men.Key words:Male infertility, antioxidants, L-carnitine, azoospermia.
Keywords: Male infertility; antioxidants; Lcarnitine; azoospermia